A PROCESS-ORIENTED MODEL FOR THE FORMATION OF SELF-EXPRESSION SKILLS IN TEACHING MUSIC TO PUPILS OF THE PRIMARY EDUCATION STAGE - Kepule, Iveta; Strode, Aina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The concept of self-expression is used to describe contemporary culture, linking it to positive concepts, the interaction of the individual and the environment. Emotional and cognitive needs, based on personal experience, cultural and environmental situations and events in a rapidly changing social environment, play an important role in the development of self-expression skills. An aim of the article: to substantiate the process-oriented model of pupil self-expression skills formation and to analyze its approbation results - pupil learning achievement dynamics and learning process transformation in music education. Research methods: analysis of scientific literature, analysis of documents, statistical analysis of learning achievements.